An evaluation of services the Mara Liner Bus Company problems and solutions - Abdullah, Muhammad Hanif; Aziz, Zulkufli (2012)
The research has been carried out to make an evaluation the services of Mara Line Bus Company as a public transportation in Universiti Utara Malaysia.Through of the study, some negative factors influencing the development and the effectiveness of the present public transport system have been identified.To overcome these problems, some suggestion has to implement.The findings of the research among others were reviewed the problems of the products, competition and the workers of Mara Liner Bus Company and provide transport services for UUM students. The MARA Liner Bus Company should provide more buses to UUM, reduce the ticket price, fix a specific number of passengers, the conductors is not friendly and so on.This research also is going to evaluate the problems of public transport in Malaysia and the way to solve the negative effect in the future.